2011
DOI: 10.1186/1471-2458-11-662
|View full text |Cite
|
Sign up to set email alerts
|

A registry-based follow-up study, comparing the incidence of cardiovascular disease in native Danes and immigrants born in Turkey, Pakistan and the former Yugoslavia: do social inequalities play a role?

Abstract: BackgroundThis study compared the incidence of cardiovascular disease (CVD) and acute myocardial infarction (AMI) between native Danes and immigrants born in Turkey, Pakistan and the former Yugoslavia. Furthermore, we examined whether different indicators of socioeconomic status (SES), such as employment, income and housing conditions influenced potential differences.MethodsIn this registry-based follow-up study individuals were identified in a large database that included individuals from two major regions in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 35 publications
2
23
0
Order By: Relevance
“…Similar findings have previously been reported in the general population [22][23][24]; here we have shown this for the first time in a population with diabetes and demonstrated that the excess risk persists even after full statistical adjustment for BMI, metabolic, lifestyle, SES and disease factors. Independent of the effect of age and age of diabetes diagnosis, rates of CVD differed among the various ethnic groups.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Similar findings have previously been reported in the general population [22][23][24]; here we have shown this for the first time in a population with diabetes and demonstrated that the excess risk persists even after full statistical adjustment for BMI, metabolic, lifestyle, SES and disease factors. Independent of the effect of age and age of diabetes diagnosis, rates of CVD differed among the various ethnic groups.…”
Section: Discussionsupporting
confidence: 74%
“…Other studies reporting ethnic differences were conducted in the general population and used diabetes as an adjustment factor [8,[22][23][24] rather than investigating ethnic differences among people with diabetes. Studies performed in people with type 2 diabetes were small to modest cohort studies (n=4,974) [11,12,28,38,41,42] or combined different ethnic groups (Pakistani, Indian, Bangladeshi and Sri Lankan) as one group of South Asians [8,12,24,26,28,38,42].…”
Section: Discussionmentioning
confidence: 99%
“…20,21,24,26,27,29,31,34 Among first-generation immigrants, although there was some heterogeneity across these studies, immigrants from Eastern and some other Western European countries, the Middle East, and South Asia were found to be at an overall greater risk than the host population, and those from Africa and North America were at lower risk. Notably, male immigrants to Sweden from other Nordic countries (eg, Finland), Eastern Europe, the Middle East, and Asia had particularly greater incidence of IHD than the host male population.…”
Section: Immigrants Vs Host Populationsmentioning
confidence: 89%
“…An increased incidence for cardiovascular disease (CVD) was found among Turkish and Pakistani immigrants but similar incidence found among former Yugoslavian immigrants compared with ethnic Danes. Likewise, an increased incidence of Acute Myocardial infarction was found for Turkish immigrant men and Pakistani immigrant men and women while a similar incidence for Turkish immigrant women as well for former Yugoslavian men and women was seen compared with ethnic Danes [18]. Self-reported high blood pressure and heart issues were more common in immigrants than in ethnic Danes [2] in one study; in another study, no differences were detected [19].…”
Section: Adultsmentioning
confidence: 94%